Gambaran Perilaku Makan dan Berat Badan Mahasiswa di Masa Pandemi Covid-19 - Huda, Ramadhan Khairul; Fatmawati, Tina Yuli; Chandra, Filius; Kasyani, Kasyani (Prosiding Seminar Kesehatan Nasional, 2023)
One of the effects of the COVID-19 pandemic on students is online learning (learning from home). The pandemic can increase stress and appetite which can lead to changes in eating behavior and a person's nutritional status. The purpose of this study is to describe the eating behavior and weight of the students during the pandemic of Covid-19. This study is quantitative descriptive research with a cross-sectional design. The population in this study was 573 regular students A, and the samples were 94 students. The sampling technique used in this study is accidental sampling. The variables of this study were eating behavior and body weight which were analyzed using a frequency distribution. The majority of students (77.6%), when they were at home during theCovid-19 pandemic, stated that their appetite had increased; namely, 25.5% said "always", and 52.1% said "often". Based on other people's assessments and changes in the tightness/looseness of clothing, the majority of students (73.4%) during the pandemic experienced a change in weight; namely, 62.8% experienced an increase, and only 10.6% experienced a decrease. There was a change in student eating behavior and weight during the COVID-19. Students are expected to be able to improve their eating behavior and control their weight.Â